MOTIF DAN MAKNA DIRI SEBAGAI ATLET SEPAK TAKRAW PUTRI PENGURUS PROVINSI RIAU - Ema Sularsih; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Generally, Takraw sports is done by men because it needs physical strength and special techniques in the game. But now the paradigm that must be dichotomized between masculine male sports and feminine women's sports has been overhauled as soccer takraw is now increasingly in demand by women and has been contested at regional , national and international level. Becoming a female sepak takraw is not an easy profession. In fact, there is no woman who was born and named instantly as an athlete. The aim of this research is to idemtify the motive, the self-meaning and the meaning of sepak takraw profession for female sepak takraw atlete Pengurus Province (Pengprov) RiauThis study uses a qualitative research method with the study of Phenomenology. The subject of this research was ten of female sepak takraw athletes Pengurus Province (Pengprov) Riau that was chosen by snowball technique. The data collection technique was collected through interview, observation, and research documentation. This study uses data analysis techniques ranging from data collection, data reduction, data presentation and drawing conclusion. To achieve the validity of data in this study, researcher used extension of participation and triangulation.The results showed first, the motive of female  sepak takraw athletes Pengurus Province Riau consisted of motives because namely motivated by others, curiosity, and encouragement of parents, while the in order to motive on the takraw female athletes were  proud parents ,becoming takraw coaches, better achievements, want to be a sepak takraw motivation and self-proof. Secondly, female sepak takraw  athletes Pengurus Province Riau interpreted themselves as a great women, as independent women and as women with achievements. Thirdly, sepak takraw female athletes Pengurus Province Riau defines that this sepak takraw female profession is as a sport that produces, unique sports, extreme but fun sports and sports that can increase self-confidence. Keywords: Female Sepak Takraw, Motive, Selft Meaning, Meaning of